Gnostyk heterodoksyjny i prawdziwy gnostyk w Chrystusie według nauczania Ireneusza z Lyonu - Artemi, Eirini (Vox Patrum, 2018)
The fight against gnostics allowed the holy bishop to develop the Christian doctrine with a perfect way. At first, he showed that the knowledge that heretics sought in vain in mythical narratives was not real. The only real gnosis was love and grace for believers in Christ and they were given to them by the Holy Spirit. Only in Church man can be saved. And the real “gnostics” were not those who rejected and despised their body in order to worship an “incomprehensible God” and “Creator,” but the “spiritual” people who received from the Holy Spirit the resurrection of the flesh and its indestructibility.